Application of a Modified Low-Field NMR Method on Methane Adsorption of Medium-Rank Coals. (5th March 2021) - Chen, Xiaozhen; Yan, Taotao; Zeng, Fangui; Meng, Yanjun; Liu, Jinhua
Abstract : Methane adsorption capacity is an important parameter for coalbed methane (CBM) exploitation and development. Traditional examination methods are mostly time-consuming and could not detect the dynamic processes of adsorption. In this study, a modified low-field nuclear magnetic resonance (NMR) method that compensates for these shortcomings was used to quantitatively examine the methane adsorption capacity of seven medium-rank coals. Based on the typical T 2 amplitudes obtained from low-field NMR measurement, the volume of adsorbed methane was calculated. The results indicate that the Langmuir volume of seven samples is in a range of 18.9–31.85 m 3 /t which increases as the coal rank increases. The pore size in range 1-10 nm is the main contributor for gas adsorption in these medium-rank coal samples. Comparing the adsorption isotherms of these coal samples from the modified low-field NMR method and volumetric method, the absolute deviations between these two methods are less than 1.03 m 3 /t while the relative deviations fall within 4.76%. The absolute deviations and relative deviations decrease as vitrinite reflectance (R o ) increases from 1.08% to 1.80%. These results show that the modified low-field NMR method is credible to measure the methane adsorption capacity and the precision of this method may be influenced by coal rank.